IDNLearn.com provides a collaborative environment for finding and sharing answers. Join our interactive Q&A community and access a wealth of reliable answers to your most pressing questions.

The sum of present ages of two persons is 50 years. If younger person becomes the age of the older one that time sum of their ages will be 90 years, find their present ages..​

Sagot :

Answer:

35, 15

Step-by-step explanation:

Let the present age of the younger person = x

Then the present age of the older person = 50 - x

After (50 - x) - x years, the younger person will be x + [(50 - x) - x} = 50 - x, the older person will be 50 - x + (50 - x) - x = 100 - 3x

Theire age sum will be (50 - x) + (100 - 3x) = 90

150 - 4x = 90

4x = 150 - 90 = 60

x = 60/4 = 15

50 - x = 35